Globally Stable Periodic Solution of Certain Fourth Order Non-Linear Differential Equations - Ogundare, B. S. (2014)
In this paper, we give criteria for the existence of a unique solution to a certain fourth order nonlinear differential equations which is bounded together with its derivatives on the real line, globally stable and periodic by the use of a complete Lyapunov function.